Visual Representation Ability of Junior High School Students on Quadrilateral Material - Sabila Mukhlishonisa; Al Jupri; Jarnawi Afgani Dahlan (proceedings.icesy, 2026)
Visual representation ability is an important competency in mathematics learning, especially in geometry. Visual representation helps students transform abstract concepts into concrete forms, thereby facilitating the problem-solving process. This study aims to describe junior high school students’ visual representation ability in solving quadrilaterals problems. This study used a qualitative approach with a descriptive method. The research subjects were eight-grader junior high school students that were given five essay questions about quadrilateral material. The data were analyzed based on a visual representation scoring rubric. The results represented by five students who were purposely selected. It showed that one student had moderate visual representation ability, while four students were in the high category. These findings indicate that visual representation ability play an important role, errors in visual representation tend to have a direct impact on errors in problem solving. Therefore, visual representation ability needs to be developed systematically in mathematics learning.